Combinational protective therapy for spinal cord injury medicated by sialic acid-driven and polyethylene glycol based micelles. (October 2019) - Wang, Xiao-Juan; Shu, Gao-Feng; Xu, Xiao-Ling; Peng, Chen-Han; Lu, Chen-Ying; Cheng, Xing-Yao; Luo, Xiang-Chao; Li, Jie; Qi, Jing; Kang, Xu-Qi; Jin, Fei-Yang; Chen, Min-Jiang; et al.
Abstract: Spinal cord injury (SCI) leads to immediate disruption of neuronal membranes and loss of neurons, followed by extensive secondary injury process. Treatment of SCI still remains a tremendous challenge clinically. Minocycline could target comprehensive secondary injury via anti-inflammatory, anti-oxidant and anti-apoptotic mechanisms. Polyethylene glycol (PEG), a known sealing agent, is able to seal the damaged cell membranes and reduce calcium influx, thereby exerting neuroprotective capacity. Here, an E-selectin-targeting sialic acid - polyethylene glycol – poly (lactic-co-glycolic acid) (SAPP) copolymer was designed for delivering hydrophobic minocycline to achieve combinational therapy of SCI. The obtained SAPP copolymer could self-assemble into micelles with critical micelle concentration being of 13.40 μg/mL, and effectively encapsulate hydrophobic minocycline. The prepared drug-loaded micelles (SAPPM) displayed sustained drug release over 72 h, which could stop microglia activation and exhibited excellent neuroprotective capacity in vitro . The SAPP micelles were efficiently accumulated in the lesion site of SCI rats via the specific binding between sialic acid and E-selectin. Due to the targeting distribution and combinational effect between PEG and minocycline, SAPPM could obviously reduce the area of lesion cavity, and realize more survival of axons and myelin sheaths from the injury, thus distinctly improving hindlimb functional recovery of SCI rats and conferring superior therapeutic effect in coparison with other groups. Our work presented an effective and safe strategy for SCI targeting therapy. Besides, neuroprotective capacity of PEG deserves further investigation on other central nervous system diseases. Graphical abstract: Image 1